The Effect of Visitor Satisfaction on Revisit Intention at Embun Waterpark Pasaman - Muhammad Ikhsan; Feri Ferdian (Journal of Multidimensional Management, 2026)
This study examines the effect of visitor satisfaction on revisit intention at Embun Waterpark in Pasaman Regency, Indonesia. The research was motivated by increasing visitation alongside complaints about the visitor experience and indications that some visitors were reluctant to return. A quantitative cross-sectional causal-associative survey was conducted between October and November 2022 among 241 visitors who had visited the attraction at least twice. Respondents were selected through purposive sampling and completed a five-point Likert-scale questionnaire. Satisfaction was measured through fulfillment of expectations, needs, and desires, while revisit intention was represented by intention to revisit, recommendation, and destination preference. Simple linear regression showed that satisfaction was positively associated with revisit intention (B = 0.247, beta = 0.376, t = 6.264, p < 0.001). The model explained 14.1% of the variance in revisit intention. The findings indicate that satisfaction is a meaningful but limited predictor of return intention, so destination management should improve the visitor experience while also addressing other determinants of loyalty.